The Role of High Pressure Processing in Maintaining Microbiological Safety and Flavor of Fresh and Minimally Processed Foods: A Mini Review - Prayitno, Citra Pratiwi; Defira, Citra; Ichsan, Onne Akbar Nur; Sujatmiko, Harumi; Saputra, Doris; Lestari, Windi; Aldoni, M. (Journal of Food and Agricultural Product, 2025)
The microbiological safety of fresh food products is a crucial challenge in the food industry, mainly due to the high prevalence of pathogenic microorganisms such as Salmonella spp., Escherichia coli, and Listeria monocytogenes. At the same time, there is an increase in consumer demand for fresh products with optimal organoleptic and natural nutritional qualities. High-Pressure Processing (HPP), as a non-thermal processing technology, offers an innovative solution to these problems. This mini review aims to examined the basic principles of HPP, its effectiveness in inactivating microorganisms, and its impact on the sensory attributes of various fresh food products. Various studies show that HPP can significantly reduce the number of microbes while maintaining the organoleptic characteristics of fresh food products. Overall, HPP shows great potential as a future food processing technology that can bridge the need for safety and quality in fresh products. Keywords: High-Pressure Processing, food products, fresh food